A Sociological Perspective on Morrison’s Translation Work in China - Duan, Jiayi (Integrated Journal for Research in Arts and Humanities, 2024)
During his twenty-five years of missionary work in China, Robert Morrison creatively engaged in activities such as translating the Bible, compiling the Chinese-English Dictionary, and founding the periodical of the Anglo-Chinese Evangelization Society. He made the acquaintance of and employed Chinese engravers, printers, and language teachers like Yong Sam Tak, Leang-Kung-fah, Tase-a-ko, and Kew-agong, and conducted various translation activities in China. This article, from the perspective of social translation studies, explores the structure and dissemination of Morrison's translation endeavors in China from a macro perspective. Using Latour's Actor-Network Theory (ANT) to analyze both human and non-human actors, and supplementing it with Bourdieu's social theory, this study reveals how Morrison mobilized and coordinated these actors to advance his translation projects. Ultimately, this forms a complete closed loop of Morrison's translation network in China, providing insights for translation activities, sinology, and translation studies during the period of Sino-Western cultural exchange.